Transliteration engine for union catalogue of Malay manuscripts in Malaysia: E-Jawi version 3 - Abdul Razak, Sitti Munirah; Abu Seman, Muhamad Sadry; Wan Mamat, Wan Ali @ Wan Yusoff; Mohammad Noor, Noor Hasrul Nizan (IEEE, 2018)
There are several online transliteration tools in web version available for modern Jawi to Rumi and vice versa, however is not available for old Jawi, which was widely used in old Malay manuscripts. E-jawi is one of the well-known Malay- Jawi and Jawi-Malay transliteration tools available online, besides Dewan Bahasa dan Pustaka (DBP) Daftar Rumi-Jawi Beta which transliterate modern jawi terms into rumi and vice versa. This paper aims to review the background of E-Jawi as one of the popular tools available online and the method used by E-Jawi version 3 which is the combination of two methods: E-Jawi Transliteration Database and E-Jawi Algorithm Technique); to compare the results of transliterating old manuscript terms both in old jawi and its modern jawi form (obtained from Daftar Kata Bahasa Melayu: Rumi-Sebutan-Jawi) using E-Jawi; and to propose an initial architecture of text mining tool for transliteration part, which will integrate with E-Jawi as part of its transliteration engine. The pilot data used is extracted from Bidāyat al-Mubtadī bi-Faḍlillāh al-Muhdī manuscript. The research found that E-Jawi has low error percentage for modern jawi and there are some enhancements that can be done in supporting transliteration for old jawi as well as to improve the transliteration for modern jawi. All the findings shall contribute to the development of Union Catalogue of Malay Manuscript (UCMM) catalogue system, which targets to provide an informative platform consisted of old manuscript corpus for Malay Manuscript researchers as well as text mining tool for mining of Manuscripts data.